Synthesis of novel β-amino ketones containing a p-aminobenzoic acid moiety and evaluation of their antidiabetic activities - Tang, GuangXia; Yan, JuFang; Fan, Li; Xu, Jin; Song, XiaoLi; Jiang, Li; Luo, LingFei; Yang, DaCheng (Science China. Chemistry, 2013)
The synthesis of two series of [3-amino ketones containing a p-aminobenzoic acid moiety （TM.1 and TM-2） using a modified protocol of the Mannich reaction is reported. The molecular structures of a total of tweenty three new target compounds were characterized by ~H NMR, 1~C NMR, ESI-MS and HR-MS. Subsequently, their antidiabetic activities were screened in vitro. The c~-glucodase inhibition （c~-GI） activity of compound le reached a remarkable level of 66.50%. The peroxisome proliferator- activated receptor （PPAR） relative activation activities of six compounds are above 80%, and in particular 2i displays an un- precedentedly high PPAR of 130.91%. The structure-activity relationships of the compounds were established. 2i is also sub- ject to further in-depth investigation.